Prevalence and antimicrobial Susceptibility of Bacteria Isolated from Septic wounds among Patients attending Uganda Martyrs’ Hospital Lubaga. - Musoke, Richard; Musisi Lubowa, Nathan (Student’s Journal of Health Research Africa, 2021)
Background: Wound infections are associated with increased morbidity and mortality. Etiologic agents of wound infections vary with geographical locations. Pathogens that infect wounds can be part of normal flora or acquired from the hospital environment. This study aimed to determine the prevalence of wound infections, investigate the profile of pathogens cultured from an infected wound and determine their antimicrobial resistance pattern to commonly prescribed antibiotics. Methodology: A prospective cross-sectional study was conducted at Uganda Martyrs’ Hospital Lubaga from March 2020 to May 2020. Swabs from different types of wounds were processed to investigate etiologic agents using the standard microbiological technique. Antimicrobial susceptibility tests were done using a simple disc diffusion technique. Results: Out of 210 wound swab samples analyzed, 125(59.5%) were culture positive. 20(16%) of the culture had mixed infections and a total of 238 bacteria were isolated from 205 cases. Staphylococcus aureus was the most frequently isolated pathogen which accounted for 94 (75.2%) of isolates followed by Proteus 11 (8.8%). The sensitivity rates of Ciprofloxacin, ceftriaxone, and gentamicin were 80.6%, 80.6%, and 74.2% respectively. Conclusions and recommendation: S. aureus and Proteus were the predominant causes of wound infections. Ciprofloxacin, ceftriaxone, and Gentamicin were the most effective drugs. Periodic surveillance of the species of bacteria involved in wound infection and determination of their antimicrobial resistance is recommended for empirical treatment.